PENGARUH SOSIO-EKONOMI DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA - Salsa Oka Sabrina; Muh Muhaimin; Naili Rofiqoh (JS (JURNAL SEKOLAH), 2026)
Abstract: The purpose of this study is to examine how socioeconomic status and the learning environment affect sixth-grade students' academic performance at SD Negeri Bapangan Jepara.  This study's backdrop is founded on the idea that both internal and external influences can affect academic performance, which makes a comprehensive understanding of the factors that determine academic achievement in elementary schools crucial.  This study uses a causal-associative strategy in a quantitative manner.  Using a saturation sampling strategy, all 24 students who made up the study population were included in the sample.  The dependent variable was derived from students' report card scores, and the independent factors were measured using a 4-point Likert scale questionnaire.  The validity and reliability of the questionnaire were examined, and respondents were directly given the questionnaire to complete in order to gather data.  SPSS was used for data analysis, which included hypothesis testing with partial (t) and simultaneous (F) tests, multiple linear regression to look at the impact of independent factors on academic attainment, and the traditional assumption tests (normality, multicollinearity, and heteroscedasticity).  The findings indicate that while the learning environment has no discernible partial impact on academic achievement, socioeconomic position does.  Both factors simultaneously play a major role in the diversity in kids' academic achievement.  These results demonstrate the value of family support in providing sufficient learning resources and direction, and they give parents and schools a foundation on which to improve academic interventions and instructional tactics for students. Keyword: Socioeconomic Status; Learning Environment; Academic Achievement; Elementary School Students.  Abstrak: Tujuan penelitian ini adalah untuk mengkaji bagaimana status sosial ekonomi dan lingkungan belajar memengaruhi prestasi akademik siswa kelas enam di SD Negeri Bapangan Jepara. Latar belakang penelitian ini didasarkan pada gagasan bahwa pengaruh internal dan eksternal dapat memengaruhi prestasi akademik, sehingga pemahaman komprehensif tentang faktor-faktor penentu prestasi akademik di sekolah dasar menjadi krusial. Penelitian ini menggunakan strategi kausal-asosiatif secara kuantitatif. Dengan menggunakan strategi pengambilan sampel jenuh, seluruh 24 siswa yang merupakan populasi penelitian diikutsertakan dalam sampel. Variabel dependen diperoleh dari nilai rapor siswa, dan faktor independen diukur menggunakan kuesioner skala Likert 4 poin. Validitas dan reliabilitas kuesioner diperiksa, dan responden diberikan kuesioner secara langsung untuk diisi guna mengumpulkan data. SPSS digunakan untuk analisis data, yang meliputi pengujian hipotesis dengan uji parsial (t) dan simultan (F), regresi linier berganda untuk melihat dampak faktor independen terhadap prestasi akademik, dan uji asumsi tradisional (normalitas, multikolinearitas, dan heteroskedastisitas). Temuan ini menunjukkan bahwa meskipun lingkungan belajar tidak memiliki dampak parsial yang nyata terhadap prestasi akademik, posisi sosial ekonomi berpengaruh. Kedua faktor tersebut secara bersamaan memainkan peran utama dalam keragaman prestasi akademik anak. Hasil ini menunjukkan pentingnya dukungan keluarga dalam menyediakan sumber daya dan arahan belajar yang memadai, serta memberikan landasan bagi orang tua dan sekolah untuk meningkatkan intervensi akademik dan taktik pengajaran bagi siswa. Kata Kunci: Status Sosial Ekonomi; Lingkungan Belajar; Prestasi Belajar; Siswa Sekolah Dasar.